Greater similarity of conscientiousness scores in dyads is associated with greater interpersonal neural synchrony while completing a goal-oriented task: a brief report - Stoyanova, Vyara; Ashwin, Chris; Scarampi, Chiara; Hijazy, Muhammad; Carter, Felix; Stothart, George; Hinvest, Neal (Frontiers in Human Neuroscience, 2025)
Interpersonal neural synchrony provides a neural index of how individuals align cognitively and socially during interaction. While previous work has shown that personality traits shape interpersonal behavior, and that trait similarity can enhance dyadic coordination, little is known about whether such similarity predicts neural synchrony. The present study used an electroencephalography (EEG) hyper-scanning methodology to investigate the relationship between the degree of similarity in Big 5 scores of interacting participants in dyads and their interbrain synchrony during naturalistic dialogue. A total of 23 female dyads completed the Big 5 questionnaire and performed a goal-oriented social task while each wearing lightweight EEG headsets. Similarity for each Big 5 personality scale was created by calculating the absolute difference between the two participants within each dyad. Interpersonal neural synchrony was measured using Dynamic Time Warping (DTW), which quantified the similarity between separate temporal signals, based on a time-frequency decomposition of EEG. Results showed that similarity of Conscientiousness scores within dyads significantly predicted interpersonal neural synchrony within dyads (with openness showing marginal prediction). No relationship was evident for any other Big 5 trait. These findings demonstrate that personality similarity, particularly in conscientiousness, contributes to interpersonal neural synchrony, highlighting a trait-based pathway through which social alignment emerges during naturalistic interaction.